Estimation of LET distributions of α -particles from measured scintillator-based trajectory images - Seiichi Yamamoto; Kohei Nakanishi; Katsunori Yogo; Masao Yoshino; Kazuaki Tsukada; Hidetoshi Kikunaga; Takuya Yokokita; Kenji Shirasaki; Kei Kamada; Akira Yoshikawa; Jun Kataoka (Physics in Medicine & Biology, 2026)
Abstract Objective . Linear energy transfer (LET) measurements of α -particles are increasingly important for micro-dosimetric evaluation in targeted α -radionuclide therapy. However, direct LET measurements remain challenging due to the extremely short range of α -particles in matter. In this study, we propose a method to estimate LET distributions using quenching effects observed in α -particle trajectory images. Approach. α -particle trajectories were imaged using an ultra-high-resolution imaging system consisting of a Gd 3 Al 2 Ga 3 O 12 scintillator, an optical magnification unit, and an electron-multiplying charge-coupled device camera. α -particles from three radionuclides were measured: Am-241 (5.5 MeV), Po-213 (8.4 MeV) and Po-212 (8.8 MeV). LET distributions were estimated by taking the ratio of simulated dose profiles (without quenching) to measured depth profiles of α -particle trajectory images (including quenching). The estimated LET distributions were then compared with those obtained from simulations. Main results . The relative LET distributions along the depth direction were successfully estimated from the measured depth profiles for all α -particles with different energies. The estimated relative LET distributions differed from the simulated distributions by no more than 11%–24% over the depth range from 5 µ m to the Bragg peak position. Approximate absolute LET distributions were also evaluated. Significance . The proposed method enables a simple and effective estimation of LET distributions of α -particles from measured depth profiles of trajectory images. It is applicable to α -particles with a wide range of energies and has potential for advancing micro-dosimetry in targeted α -radionuclide therapy.